The effect of foreign direct investment and exchange rate on the gross domestic product in Nigeria (West African Journal on Sustainable Development, 2024)
Foreign Direct Investment has traditionally been a crucial driver of economic growth in many nations, including Nigeria during a certain period in its history. Regrettably, the influence of this investment can vary based on the prevailing exchange rate. With this in view, this study employs econometric methods to empirically examine the relationship between foreign direct investment, exchange rates, and Gross Domestic Product (GDP) in Nigeria from 1981 to 2021. The annual data was sourced from the Central Bank of Nigeria's statistical bulletin and the World Bank Development Index. The time series data collected from the Central Bank of Nigeria was subjected to various tests to ensure its reliability, including stationarity testing and a sensitivity analysis that encompassed the Ramsey Reset specification, detection of serial correlation, identification of heteroskedasticity, and evaluation of multi-collinearity.Using the Auto-Regressive Distributed Lag (ARDL) co-integration approach, the analysis revealed a significant long-term relationship between GDP and the exchange rate, while the relationship between GDP and foreign direct investment was not statistically significant. Furthermore, the models were found to be free from serial correlation and exhibited stability, making the results suitable for policy considerations. In light of these findings, it is recommended that policymakers explore diversifying their investments into other industries to attract foreign investors. Additionally, it is advised that the Central Bank of Nigeria implement stringent controls on foreign exchange policies to ensure the proper determination of the Naira's value relative to other currencies.
Keywords: Foreign Direct Investment; Exchange Rate; Inflation Rate; Real Gross; Domestic Product; Foreign Aid